2016
DOI: 10.1259/bjr.20150822
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric femur fractures at the emergency department: accidental or not?

Abstract: Only a small proportion of all paediatric fractures is caused by child abuse or neglect, especially in highly prevalent long bone fractures. It can be difficult to differentiate abusive fractures from non-abusive fractures. This article focuses on femoral fractures in young children. Based on three cases, this article presents a forensic evidence-based approach to differentiate between accidental and non-accidental causes of femoral fractures. We describe three cases of young children who were presented to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 39 publications
2
8
0
9
Order By: Relevance
“…As a consequence, infant bones do not need much force to be fractured and femur fractures in children can be caused by low-velocity incidents or by an indirect impact [ 31 ]. Spiral fractures are not specific for inflicted trauma/neglect; their presence merely implies that fracture was caused by a torsional force and may be a result of minimal force [ 1 , 32 ]. Pierce et al [ 33 ] used a biomechanical model on femur fractures in children who fell down the stairs and showed that transverse and short oblique fractures were associated with almost tenfold higher injury biomechanical measures compared to spiral and bucket handle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, infant bones do not need much force to be fractured and femur fractures in children can be caused by low-velocity incidents or by an indirect impact [ 31 ]. Spiral fractures are not specific for inflicted trauma/neglect; their presence merely implies that fracture was caused by a torsional force and may be a result of minimal force [ 1 , 32 ]. Pierce et al [ 33 ] used a biomechanical model on femur fractures in children who fell down the stairs and showed that transverse and short oblique fractures were associated with almost tenfold higher injury biomechanical measures compared to spiral and bucket handle fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 Typology of cases of maltreatment, its consequences, and outcome "bone fractures" according to the sex of the victims (according to the type of violence, the environment, the presence of fractures, the type of fracture, whether there was consultation with an orthopedist and whether there was a need for surgery or deaths), SINAN Corroborating national and international research, 2-6,12 neglect (53.9%) and physical aggression (39.1%) were the most prevalent typologies, with similar distribution between genders. The high prevalence of the latter may be related to the use of physical force as a form of "education" or disciplinary practice, 1,2,12 where parents who were raised through punishment and physical punishment perpetrate this culturally accepted habit, 1,2 regardless of the existence of public policies, such as Law No. 13,010-"Lei do Menino Bernardo" (Bernardo Boy Law) 27 or the Statute of the Child and Adolescent.…”
Section: Variablesmentioning
confidence: 99%
“…A suspeita deve ser aventada com cautela quando as lesões não correspondem ao mecanismo de trauma ou à história declarada. 2,3,6,7,12,13 Danos térmicos, lesões inexplicáveis de tecidos moles ou no crânio, fraturas nas costelas e/ou múltiplas, atraso na busca de atendimento médico ou qualquer lesão em uma criança que ainda não anda, devem chamar a atenção do profissional de saúde. [2][3][4]7 Lesões na coluna são raras em crianças, mas que podem acontecer em vítimas de violência.…”
Section: Introductionunclassified
See 2 more Smart Citations